Price Distortion and Shortage Deformation or What Happened to the Soap - Weitzman, Martin L. (American Economic Review, 1991)
The model of this paper generalizes the classical theory of consumer behavior to the more general case of prices that are not necessarily market-clearing. Suppose that, in addition to the money cost, some sort of search, waiting, or other quasi-fixed "effort cost" is needed to obtain goods. The presence of this quasi-fixed cost element will trigger an inventory policy. A shortage equilibrium occurs when effort costs are such that, in the corresponding inventory policy, the flow of desired consumption does not exceed the available supply flow. Stock hoarding, a critical phenomenon in the economics of shortage, emerges as a natural component of this model. A complete characterization of a stationary shortage equilibrium is given. Comparative statics and welfare analysis are performed. The dynamic transition between steady states is analyzed to give insight into the mechanics of how shortages develop. Copyright 1991 by American Economic Association.